170k views
0 votes
Let f(x)=x2−9 ​ and g(x)=x2−7x+12 .

What is (fg)(x) ?




x−4/x+3 where ​ x≠−3,4 ​

x−4/x+3 where x≠−3,3

x+4/x−3 where ​ x≠−3,3 ​

x+3/x−4 where x≠3,4

Let f(x)=x2−9 ​ and g(x)=x2−7x+12 . What is (fg)(x) ? x−4/x+3 where ​ x≠−3,4 ​ x−4/x-example-1
User Ewan Leith
by
5.4k points

1 Answer

3 votes


f(x)=x^2-9 , g(x)=x^2-7x+12

We need to find
(f)/(g)(x)


(f)/(g)(x)=(f(x))/(g(x))

We replace f(x) and g(x)


(f)/(g)(x)=(f(x))/(g(x))=(x^2-9)/(x^2-7x+12)

Now factor the numerator and denominator and simplify it


(x^2-9)/(x^2-7x+12)


((x+3)(x-3))/((x-3)(x-4))

Cancel out x-3


((x+3))/((x-4)) where x not equal to 3,4

User JM At Work
by
5.7k points